Detection in soil of a deletion in an engineered DNA sequence by using DNA probes. - Jansson, J K (1989)
Two Pseudomonas strains were engineered to contain the nptII gene and plasmid vector sequences in their chromosomes. After incubation of these strains in nonsterile soil, total bacterial DNA was isolated and analyzed by Southern blot hybridization with the nptII gene and the plasmid vector as probes. In addition to the expected bands of hybridization, a new band corresponding to the loss of vector sequences from the chromosome while retaining the nptII gene was observed for one of the strains. The more stressful conditions encountered in soil appeared to increase the frequency of loss of the vector sequences from this strain.